Review and analysis of reach stacker models for handling operations in indust - Hurieiev, Kostiantyn; Kibalenko, Vladyslav; Nikolaienko, Denys (КНУБА, 2024)
The use main advantages and disadvantages of reach stackers for container overload in port facilities and overloading complexes are defined in the paper. The review and analysis of reach stacker models of leading manufacturers was carried out. Based on this analysis, the reach stacker model to 45 tons carrying capacity was adopted as an analog for further design development.
Keywords: reach stacker; handling operations; container; tier; carrying capacity; 621.86./.87